Monitoring of Two Major Pests of Teak in Intensively Managed Plantation through Light Trap Study - Loganathan, J.; Soman, P.; Maragatham, S. (Indian Forester, 2001)
The population dynamics of both Teak defoliator, Hyblaea puera Cramer (Lepidoptera: Hyblaeidae) and Teak skeletonizer, Eutectona machaeralis (Walker) (Lepidoptera: Pyralidae) were studied in intensively managed Teak plantation in Sangamvalasa, Vizhianagaram District (Andhra Pradesh) for the years 1996 and 1997 by installing light traps. The results showed that defoliator moth catch peaked during April-July while skeletonizer occurred throughout the year with two peaks but not corresponding to any specific time of the year. The interaction between the occurrence of these two pests showed spatial and temporal variations. The weather factors when correlated with the pests showed signincant positive influence of rainfall and negative influence of wind velocity of defoliator occurrence. No specific correlation was found with skeletonizer incidence.